Korelasi Kemampuan Berpikir Kritis dan Kreatif Matematis dengan Kemampuan Pemecahan Masalah Matematis Materi Bangun Ruang - Rizki Dwi Siswanto; Rega Puspita Ratiningsih (Universitas Muria Kudus, 2020)
This research is a quantitative correlational study which aims to determine the contribution of students' mathematical creative and critical thinking skills in solving mathematical problems in building materials. The sample of this study were students of class VIII SMP Negeri 1 Warunggunung in the even semester of the 2019/2020 school year totaling 30, consisting of 8 male and 22 female who were determined by random sampling technique. The instrument used was a questionnaire of mathematical critical thinking skills, mathematical creative thinking skills and mathematical problem solving skills that had been tested for validity and reliability. The prerequisite test used is the normality test using the Kolmogorov-Smirnov method, the multicollinearity test and the heteroscedasticity test. Data analysis using simple and multiple linear regression analysis with a significant level of 5%. hypothesis testing using t-test. The results that obtained: 1) there is a contribution of critical thinking skills to problem solving abilities, and 2) there is a contribution of creative thinking skills to problem solving abilities.